Marketing Strategy So that Buyers Immediately Decide to Buy On Tiktok - Diana Novita; Roy Budiharjo; Novawiguna Kemalasari; Muhammad Laras Widyanto; Sri Kurniawati (Jurnal Pengabdian Masyarakat Formosa, 2022)
The right marketing strategy should match the media you use. In particular, marketing activities can now be performed through a variety of media platforms, so this condition requires caution when planning marketing procedures. The motive of advertising is to trade the delivered cost that exists as many consumers as feasible, as regularly as feasible in order that consumers earnings and dealers’ earnings, so to "Exchange" we want to "Offer." The maximum crucial factor in a enterprise isn't an office, now no longer technology, now no longer a products or services however the `Offer'. Primarily based totally on that we're in the end glad that the trouble that arises is how it may be understood and implemented in our enterprise in order that customers can come and purchase from us and what platform are we able to use? We perform these studies primarily based totally at the discourse in books, clinical magazines and additionally journals approximately advertising techniques that we read. The studies that we use is primarily based totally on a survey that we performed via the Google Survey Form.